A Membraneless Electrochemically Mediated Amine Regeneration for Carbon Capture - Ahmad Hassan; Mohsen Afshari; Mim Rahimi (Nature Communications)
Abstract Electrochemical carbon capture (ECC) processes offer efficient, scalable, and modular alternatives to conventional thermal-based methods. Among ECCs, electrochemically mediated amine regeneration (EMAR) reached higher technology readiness levels, moving from small-scale laboratory studies toward pilot-scale implementations. Previous EMAR systems rely on ion-selective membranes, which contribute significantly to the cost and present challenges for long-term operation. This study presents a membraneless EMAR system by fundamentally redesigning the process configuration and using gas diffusion electrodes (GDEs) as both the anode and cathode. This setup eliminates the membrane and the need for additional equipment such as the absorption column, flash tank, and pumps, significantly reducing the process footprint and simplifying the flow diagram. Two GDE configurations, mesh-attached and electrodeposited, are tested and compared in terms of CO2 removal efficiency, current density, and energy consumption. Electrodeposited GDEs achieve CO2 removal efficiencies above 90% with energy consumption as low as 60 kJ/mol CO2. A techno-economic analysis estimates a levelized cost of capture of ~$70/tonneCO2, compared to $137/tonneCO2 for conventional EMAR. Further improvements in current density and removal efficiency may enable costs below $50/tonneCO2. These results position the membraneless EMAR as a potentially promising approach for cost-effective and scalable point-source carbon capture.